Trends of International Trade in Services: Integration Opportunities for Ukraine - Bodnarchuk, Tetyana; Lysak, Volodymyr (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
In the article the main trends and patterns of the development of international trade in services in the period of post-industrial development of the world economy are considered. Ukraine’s competitive positions on international service market are outlined. The main endogenous factors of enhancing the country’s integration to the world trade relations system in service sector are determined